Beyond Remembering: Assessment and Evaluation of Middle School Mathematics Learning within the Framework of Bloom's Taxonomy - Oktaviana Nirmala Purba; I Gede Ratnaya; I Dewa Ayu Made Budhyani; I Gusti Lanang Agung Partawa (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Mathematics assessment in junior secondary schools should respond to students’ diverse cognitive attainment across Bloom’s Taxonomy, from C1 to C6. However, studies indicate that assessment instruments in textbooks, exercises, daily tests, and end-of-semester examinations remain dominated by C1–C3 questions and inadequately support higher-order thinking skills. This article examines the alignment of mathematics assessment practices with the responsiveness principles of Bloom’s Taxonomy. The study employed a qualitative approach using secondary data and a critical qualitative review design. Data came from articles, research reports, and review documents indexed in Google Scholar, ERIC, and arXiv, and were analysed thematically and critically. The findings reveal a gap between HOTS-oriented curriculum expectations and the cognitive distribution of questions. In one Year 7 mathematics textbook, C2 questions accounted for 75.2%, whereas C6 questions represented only 0.4%. These findings highlight the need for more balanced, adaptive, and responsive mathematics assessments that accommodate variations in students’ thinking abilities.